2015
DOI: 10.1007/s10439-015-1440-2
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Sensory Organization Test: How Sensory Conflict Affects the Temporal Structure of Sway Variability During Gait

Abstract: When maintaining postural stability temporally under increased sensory conflict, a more rigid response is used where the available degrees of freedom are essentially frozen. The current study investigated if such a strategy is also utilized during more dynamic situations of postural control as is the case with walking. This study attempted to answer this question by using the Locomotor Sensory Organization Test (LSOT). This apparatus incorporates SOT inspired perturbations of the visual and the somatosensory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 37 publications
0
24
1
Order By: Relevance
“…Our previous research with the LSOT has shown that dynamic balance control during walking in healthy individuals is affected by the manipulation of multisensory inputs. 12,13 The amount of sway variability observed during walking reflects similar balance performance with standing posture, indicating that similar feedback processes may be involved. 12 However, the contribution of visual input is significantly increased during walking in comparison to standing.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Our previous research with the LSOT has shown that dynamic balance control during walking in healthy individuals is affected by the manipulation of multisensory inputs. 12,13 The amount of sway variability observed during walking reflects similar balance performance with standing posture, indicating that similar feedback processes may be involved. 12 However, the contribution of visual input is significantly increased during walking in comparison to standing.…”
Section: Introductionmentioning
confidence: 92%
“…Sway variability measures were used as previously described to investigate dynamic postural control. 12,13 We hypothesized that the MV would affect both the amount and the temporal structure of sway variability during walking and, when applied in combination with manipulations of the visual and the somatosensory inputs, would further augment the observations from in our previous work. 12,13 …”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations